No One in Charge: A New Theory of Coordination and an Analysis of US Civil-Military Coordination in Afghanistan 2001 - 2009 - Strimling Yodsampa, Andrea. (2017)
Abstract: This dissertation challenges the argument common in the scholarly literature and policy discourse on peacebuilding that the way to achieve coordination in peacebuilding is to establish a strong, overarching coordination authority. While some degree of centralization may be possible and desirable among organizations nested within an overarching bureaucratic system, centralized coordination is not an option within the peacebuilding system writ large. The sovereign nations, non-governmental organizations, and other autonomous and semi-autonomous actors engaged in peacebuilding simply will not accept an overarching coordination authority. The dissertation argues that the question that has driven much of the literature and policy discourse - how to establish a stronger, more effective, overarching coordination authority - must be reframed. The more policy-relevant and theoretically interesting question is: How is coordination achieved when no one is charge? In posing and seeking to answer this question, the dissertation draws inspiration and insights from a small, interdisciplinary body of research that frames coordination in peacebuilding in terms of negotiation among autonomous actors, decentralized networks, and complex systems. This includes work in the fields of international relations, conflict resolution and peacebuilding, humanitarian relief, and development. Building on this prior research, the dissertation develops a new theory of coordination that emphasizes the explanatory power of multi-stakeholder processes and organizational structures and systems. It does this in three steps. First, it defines coordination in terms of results and identifies the variables hypothesized to explain coordinated results. Second, it analyzes US civil-military coordination in Afghanistan within and across four periods between 2001 and 2009. Third, it uses the empirical analysis to test the hypotheses and build a theoretical model of coordination. The dissertation concludes by identifying implications for theory, as well as for policy and practice. While the dissertation is grounded empirically in peacebuilding, the findings are potentially relevant to other contexts in which coordination is necessary but no one is in charge.; Thesis (Ph.D.)--Tufts University, 2011.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: Peter Uvin.; Committee: Eileen Babbitt, and Antonia Handler Chayes.; Keywords: International Relations, Public Policy and Social Welfare, and Peace Studies.